The Beneficial Values of Activating Quizlet Application to Escalate EFL Learners’ Vocabulary Knowledge Growth - Wijaya, Kristian Florensio (English Education Department, 2025)
In these modern second language teaching-learning enterprises, technology plays a pivotal role in shaping a deeper understanding of the targeted lessons among EFL learners. For this reason, second language educators ought to be willing to embrace the advent of digitalization in their regular classroom learning circumstances to promote more optimal educational outcomes to be further attained by language learners. This library-based qualitative study aimed to investigate the beneficial values of activating the Quizlet application to escalate EFL learners’ vocabulary knowledge growth. To embody the objective mentioned above, the researcher internalized a thematic analysis approach to yield more credible, relatable, and applicable results as the thematically-based findings were clustered into some major-specific themes. The thematically categorized research results disclosed that the Quizlet application promoted more enjoyable vocabulary learning experiences and helped EFL learners master challenging new words easily.